2019
DOI: 10.1002/jcp.28908
|View full text |Cite
|
Sign up to set email alerts
|

Zinc ions increase GH signaling ability through regulation of available plasma membrane‐localized GHR

Abstract: It is well known that zinc ion (Zn 2+ ) can regulate the biological activity of growth hormone (GH). However, until now, the mechanism by which Zn 2+ regulates GH biological activity remains unclear. In the current study, we first performed molecular docking between Zn 2+ and porcine GH (pGH) using computational biology. We then explored the effect of Zn 2+ on the GH signaling ability in the cell model expressing porcine growth hormone receptor (GHR). It was found that the phosphorylation levels of Janus kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In fact, GHR signaling pathways can be regulated at multiple levels. Li et al found that zinc ions could regulate GH/GHR signaling, which enhances GH signaling ability through regulation of available plasma membrane localized GHR 18 . Recent study has shown that nuclear‐targeted growth factors or cytokine receptors can regulate the activity of signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, GHR signaling pathways can be regulated at multiple levels. Li et al found that zinc ions could regulate GH/GHR signaling, which enhances GH signaling ability through regulation of available plasma membrane localized GHR 18 . Recent study has shown that nuclear‐targeted growth factors or cytokine receptors can regulate the activity of signaling molecules.…”
Section: Discussionmentioning
confidence: 99%